2005
DOI: 10.1177/104063870501700203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ear Notch Immunohistochemistry, Ear Notch Antigen-Capture ELISA, and Buffy Coat Virus Isolation for Detection of Calves Persistently Infected with Bovine Viral Diarrhea Virus

Abstract: Two techniques performed on skin biopsy samples (ear notches), immunohistochemistry (IHC) and antigen-capture ELISA (AgELISA), were compared for detection of bovine viral diarrhea virus (BVDV) persistent infection (PI) in 559 Angus calves between the ages of 1 and 5 months. The calves also were tested for BVDV infection using virus isolation (VI) and reverse transcription (RT)-PCR on buffy coat samples and for antibodies to BVDV types la and 2 by serum neutralization (SN). Sixty-seven of 559 (12.0%) calves tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 16 publications
3
109
3
5
Order By: Relevance
“…This method demonstrated 100% sensitivity in the detection of PI animals when used on ear notch tissue samples (Cornish et al 2005).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…This method demonstrated 100% sensitivity in the detection of PI animals when used on ear notch tissue samples (Cornish et al 2005).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…However this may be sufficient for herd health and BVD control programmes that focus on the identification of PI animals only. Furthermore, Cornish et al (2005) revealed that the antigen capture ELISA method identified 100% of PI animals in the sample population analysed when compared to a number of other diagnostic techniques. Hilbe et al (2007) reported varying antigen ELISA sensitivity and specificity values in a diagnostic method comparison.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Multiple tissues, including brain from both calves, were examined following immunohistochemical staining for bovine viral diarrhea (BVD) antigen. 11 Samples of cerebellar folia, basal ganglia, and liver from animal 1 were processed for electron microscopy and examined using a Philips 410 electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…?show "fnote_aff1"$^! "content-markup(./author-grp [1]/aff|./author-grp [1]/dept-list)> Exposure to Bovine viral diarrhea virus (BVDV; family Flaviviridae, genus Pestivirus) results in economically important diseases in cattle. 5,6 Infection with BVDV results in both persistent (a result of in utero exposure) and acute (a result of postnatal exposure) infections.…”
mentioning
confidence: 99%
“…1 The testing was performed according to the manufacturer's directions. Optical density (OD) readings were determined, and the presence or absence of BVDV antigen in each sample was determined by calculating the sample to positive (S/P) ratio for each sample according to the manufacturer's directions.…”
mentioning
confidence: 99%